ANALISIS PERMINTAAN DAN PENAWARAN LULUSAN SMK DALAM PEMENUHAN PASAR TENAGA KERJA - Perdana, Novrian Satria (Universitas Muria Kudus, 2019)
The objectives of this study are (1) to analyze DUDI demand on the competence ofvocational graduates in an effort to achieve a balance of the labor market, and (2) analyzethe supply of vocational graduates needed by DUDI in an effort to achieve a balance of thelabor market. In this study using qualitative approaches primary data analysis methods.This research was conducted in Central Java Province in 2018. The results of this studyare: (1) the qualifications of the workforce needed for DUDI in the middle to upper scaleare primarily having a certificate of competence, having IT and foreign language skills,and having experience working in the field the same for 1 year, and (2) the competencies ofvocational graduates produced have been sought to adjust DUDI's needs, but there arelimitations in the ability of vocational graduates because of the lack of facilities andinfrastructure in schools and the limited ability of educators.